High five - Evanovich, Janet (New York : St. Martin's Press, 1999)
New Jersey bounty hunter Stephanie Plum struggles to make ends meet while coping with a missing Uncle Fred, homicidal rapist and stalker Benito Ramirez, amorous vice cop Joe Morelli, and would-be lover Roger.
Accelerated Reader AR
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women detectives -- New Jersey -- Fiction; Bail bond agents -- New Jersey -- Fiction; Bounty hunters -- Fiction; Private investigators -- Fiction; Trenton (N.J.) -- Fiction; Mystery fiction